Analysis Of The Quality Of Public Services At The Neighborhood Level In The 2019 Coronavirus Disease (Covid-19) Era (Study at Pasar Bawah Subdistrict Office, Lahat District, Lahat Regency): Analisis Kualitas Pelayanan Publik Di Tingkat Kelurahan Pada Era Coronavirus Disease 2019 (Covid-19) (Studi Pada Kantor Kelurahan Pasar Bawah Kecamatan Kota Lahat Kabupaten Lahat) - Anggreani, Masayu Rika (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
The impact of the COVID-19 outbreak requires the acceleration of services with government employees working from home (WFH) as part of the concept of telecommuting (remote work activities) in the world of work and city planning. WFH in Indonesia is felt by every government organization, especially in sub-district offices, so technological acceleration in services must be optimized with these conditions. The research aims to explain the quality of public services located at the Pasar Bawah Subdistrict Office, Kota Lahat District, Lahat Regency during the post-COVID-19 pandemic. The method applied is descriptive qualitative. The theoretical analysis used is Tangibility, Reliability, Responsiveness, Assurance, and Emphaty. The results of this research include: the service process at the Pasar Bawah Subdistrict Office, Kota Lahat District, Lahat Regencies does'nt yet optimal, it's because even though the skills of the subdistrict employees are very reliable and have utilized WhatsApp technology, the community still has problems with publishing service products due to limited implementation personnel, the community do not understand the information on the requirements for public service products and have to ask directly at the Pasar Bawah sub-district office, only 1 (one) service counter is available, and there are no instructions posted around the Pasar Bawah sub-district office.